Declining home range area predicts reduced late‐life survival in two wild ungulate populations. (15th April 2018) - Froy, Hannah; Börger, Luca; Regan, Charlotte E.; Morris, Alison; Morris, Sean; Pilkington, Jill G.; Crawley, Michael J.; Clutton‐Brock, Tim H.; Pemberton, Josephine M.; Nussey, Daniel H.
Abstract: Demographic senescence is increasingly recognised as an important force shaping the dynamics of wild vertebrate populations. However, our understanding of the processes that underpin these declines in survival and fertility in old age remains limited. Evidence for age‐related changes in foraging behaviour and habitat use is emerging from wild vertebrate studies, but the extent to which these are driven by within‐individual changes, and the consequences for fitness, remain unclear. Using longitudinal census observations collected over four decades from two long‐term individual‐based studies of unmanaged ungulates, we demonstrate consistent within‐individual declines in home range area with age in adult females. In both systems, we found that within‐individual decreases in home range area were associated with increased risk of mortality the following year. Our results provide the first evidence from the wild that age‐related changes in space use are predictive of adult mortality.